Methods of evaluating dynamic characteristics of the helicopter with suspension mode vysinnya - Вовк, В.Г.; Хлюст, П.О.; Романовський, М.Д. (Proceedings of National Aviation University (archive), 2009)
The new estimating method of stochastic parameters of the complex moving object (helicopter with cargo suspension) is suggested for the structured problem identification of the object and optimal stabilizing system synthesis as well.